Analysis of Different Security Issues in Cloud Computing - Jhende, Namita; Kumar, Raghvendra; Khan, Naazish Rahim (International Journal For Research In Advanced Computer Science And Engineering, 2016)
Cloud computing is envisioned as the next generation technology. Cloud computing security or, more simply, cloud security is an evolving sub-domain of computer security, network security, and, more broadly, information security. It refers to a broad set of policies, technologies, and controls deployed to protect data, applications, and the associated infrastructure of cloud computing. In a cloud computing environment, the entire data resides over a set of networked resources, enabling the data to be accessed through virtual machines. Since these data-centers may be located in any part of the world beyond the reach and control of users, there are multifarious security and privacy challenges that need to be understood and addressed. There are a number of algorithms and methodologies available for achieving data security in cloud computing. In this paper we look at the current researches related to data security issues like integrity, Reliability and Confidentiality. in this particulars we will discuss how to secure client’s data on remote cloud Servers.